2003
DOI: 10.1352/0895-8017(2003)108<414:eaaada>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

β-Endorphin and ACTH are Dissociated After Self-Injury in Adults With Developmental Disabilities

Abstract: Relations between self-injuring behavior (SIB), the hypothalamic-pituitary-adrenal (HPA) stress axis, and response to an opiate antagonist were examined. Subjects were observed in their residential settings, while behavior was recorded. Blood was collected in the morning, evening, and immediately after SIB. Plasma beta-E was uncoupled from ACTH after SIB but not during the morning baseline. A significant number of the subjects (a) reduced their SIB at least 25% at all doses of naltrexone (NTX) and (b) reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0
1

Year Published

2008
2008
2011
2011

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 48 publications
1
30
0
1
Order By: Relevance
“…Indeed, numerous studies from many laboratories have shown that the functioning, relations, and processing of the POMC system are uncoupled or perturbed in subgroups of self-injuring individuals, resulting in different ratios of βE and ACTH, particularly under conditions of stress (Leboyer et al, 1994(Leboyer et al, , 1999Gillberg, 1995;Cazzullo et al, 1999;Sandman et al, 1990aSandman et al, , 1990bSandman et al, , 1995Sandman et al, , 1997Sandman et al, , 1999Sandman et al, , 2000aSandman et al, , 2002Sandman et al, , 2003.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, numerous studies from many laboratories have shown that the functioning, relations, and processing of the POMC system are uncoupled or perturbed in subgroups of self-injuring individuals, resulting in different ratios of βE and ACTH, particularly under conditions of stress (Leboyer et al, 1994(Leboyer et al, , 1999Gillberg, 1995;Cazzullo et al, 1999;Sandman et al, 1990aSandman et al, , 1990bSandman et al, , 1995Sandman et al, , 1997Sandman et al, , 1999Sandman et al, , 2000aSandman et al, , 2002Sandman et al, , 2003.…”
Section: Discussionmentioning
confidence: 99%
“…elevated transitional probability for SIB). Based on procedures employed in our previous studies (Sandman et al, 1997; Sandman, Touchette, Lenjavi, Marion, & Chicz-DeMet, 2003; Sandman et al, 1993) each subject was administered one of three doses of naltrexone (NTX; 0.5, 1.0 or 2.0 mg/kg, QOD) on separate weeks. Each positive treatment week was separated by a week of placebo treatment.…”
Section: Methodsmentioning
confidence: 99%
“…After a SIB episode, plasma β-endorphin levels increase and uncouple from adrenocorticotropic hormone (ACTH; Sandman et al 1997; Sandman et al 2003). Under normal circumstances, ACTH and β-endorphin levels are highly correlated, as they are both derived from the parent peptide proopiomelanocortin (Guillemin et al 1977).…”
mentioning
confidence: 99%
“…In addition, individuals with IDD exhibiting SIB have also been found to have elevated saliva cortisol levels, and cortisol levels were correlated with SIB severity (Symons et al 2003). Both the β-endorphin-ACTH uncoupling and altered cortisol levels among individuals with IDD and SIB suggest that the HPA stress axis is altered in individuals with IDD exhibiting SIB (Sandman et al 1997; Sandman et al 2003; Symons et al 2003). It is unlikely that these alterations in the stress response are generalizable to all persons exhibiting SIB.…”
mentioning
confidence: 99%
See 1 more Smart Citation